Perancangan Aplikasi Penjualan Aggregator Menerapkan Metode Waterfall - Sendyawan Nagari; Fadhil Muhammad Basysyar (STMIK Budi Darma, 2024)
The coffee shop sector in Indonesia has experienced rapid growth, with coffee consumption increasing steadily each year. In the process of selecting a coffee application, aspects such as security, ease of use, and promotional level are often primary considerations for users, as is the case with Kopi Kenangan CSB Mall. The business has been established for 4 years, founded precisely on October 14, 2019. With significant development, this Food and Beverage business has conducted transactions both offline and online through its three aggregators: Go Food, Grab Food, and Shopee Food. The issue identified from observations is the lack of daily, weekly, or monthly income calculations covering all three aggregators. This leads to a lack of review and development of this Food and Beverage business that has been operating for 4 years. The purpose of this research is to determine the extent of the influence of sales transactions through graphs in order to evaluate specific results visible in the mobile application using the Flutter programming language and the Laravel framework to help monitor shop transactions in detail. This research is conducted by applying the waterfall method and collecting data through processes such as interviews, observations, and documentation. By harnessing rapidly advancing technology, monitoring sales data through comparison via graphs aims to obtain contributions from the transaction summary application that can assist this Coffee Shop business in achieving its future targets.